Effect of lacosamide on epileptiform activity and structure-function relations in the brain of rats with chronic focal epilepsy - S. A. Litvinova; G. G. Avakyan; L. N. Nerobkova; T. A. Voronina; N. A. Gladysheva (Эпилепсия и пароксизмальные состояния, 2019)
The aim was to study the effect of lacosamide on epileptiform activity (EрA) and structure-function relations in the brain in the course of development of the epileptic system in rats with cobalt-induced chronic epilepsy. Materials and methods. To model chronic focal epilepsy, we used topical applications of cobalt on the sensorimotor zone of the rat cortex. The effect of lacosamide (20 mg/kg) on the cobalt-induced epileptiform activity was analyzed in parallel with with the monitoring of spectral-coherent changes in the brain during the development of the epileptic system (ES). Results. In the first 30 minutes after the administration, lacosamide briefly enhanced the EрA in the hippocampus and ipsilateral cortex, and also strengthened the cortical-hippocampal (at stage 1) and cortical-hypothalamic connections (at stage 2). Two hours after the drug administration, a decrease in EрA was observed at stages 1 and 2 of the ES development, especially in the contralateral cortex and hippocampus. At all frequency ranges, the level of the inter-center connections decreased (most pronounced in the cortical-hippocampal links). Conclusion. The effect of lacosamide on EрA in the rat brain with cobalt-induced epileptogenic focus is characterized by a decrease in EрA, two hours after the drug administration. This effect is most expressed in the cortex and hippocampus, and is accompanied by a decrease in the level of the corticalhippocampal connections.